1996
DOI: 10.1007/bf02002908
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant familial Mediterranean feverlike syndrome

Abstract: An Austrian family with recurrent fever syndrome is reported. Ethnicity, clinical features, and molecular studies point to a distinct clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The most frequently reported symptom is abdominal pain, which can resemble an acute abdomen in presentation and on physical examination 52 . Although the disease phenotype is classically described as inherited in an autosomal-recessive fashion, there are increasing reports of patients with only one identifiable heterozygous MEFV mutation, with clear autosomal-dominant inheritance 53 , 54 . Murine studies have confirmed that MEFV mutations observed in patients are gain-of-function, consistent with inflammatory phenotypes in patients with a single identified heterozygous variant 55 .…”
Section: Aetiology Of Autoinflammatory Diseasesmentioning
confidence: 99%
“…The most frequently reported symptom is abdominal pain, which can resemble an acute abdomen in presentation and on physical examination 52 . Although the disease phenotype is classically described as inherited in an autosomal-recessive fashion, there are increasing reports of patients with only one identifiable heterozygous MEFV mutation, with clear autosomal-dominant inheritance 53 , 54 . Murine studies have confirmed that MEFV mutations observed in patients are gain-of-function, consistent with inflammatory phenotypes in patients with a single identified heterozygous variant 55 .…”
Section: Aetiology Of Autoinflammatory Diseasesmentioning
confidence: 99%